PENGARUH KOMPETENSI TRAINER, PELATIHAN DAN SKOR KEY PERFORMANCE INDICATOR (KPI) TERHADAP KINERJA PROMOTOR DI SAMSUNG MOBILE DI WTC SURABAYA - Yuliyanto , Yofi; Setiawan, Ady; widodo, Agus purbo (JEB17 : Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of trainer competence, training, and Key Performance Indicator (KPI) scores on the performance of Samsung Mobile promoters at WTC Surabaya. The research employed a quantitative approach with a survey method through the distribution of questionnaires to 100 promoter respondents. Data were analyzed using multiple linear regression with the SPSS program. The findings reveal that trainer competence, training, and KPI scores simultaneously have a significant effect on promoter performance, with a coefficient of determination (R²) of 0.800. Partially, trainer competence has the most dominant influence, followed by training, while KPI scores show a positive but relatively smaller effect. This study indicates that improving promoter performance does not solely depend on performance evaluation through KPI, but is more strongly determined by the quality of trainer guidance and the effectiveness of training